S Studi Rasionalitas Penggunaan Antibiotika di RSUD DR. Murjani Sampit - darini kurniawati (LPPM Universitas Sari Mulia, 2021)
Background: Antibiotics are the most widely used type of drug due to the high incidence of infection in Indonesia. From the results of the preliminary study for 3 days prospectively, as many as 44 patients who received treatment, 37 patients (87%) received antibiotic therapy. There is the use of expensive antibiotics from the 3rd generation cephalosporin group, there are 4 trade names, 2 generation cephalosporins and 1 there are 6 trade names. Expensive sulbenicin and aminoglycoside derivatives are also found, Gentamicin and Kanamycin. The relatively cheap antibiotics are chloramphenicol, tetracycline, cotrimoxazole, but various brands of these products are popular with